Relationship between Self Management and Self Efficacy Towards Quality of Life in Type 2 Diabetes Mellitus Patients: Systematic Review - Rohematus Soleha; Abdul Muhith; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2025)
The implementation of self-management for diabetes mellitus patients is influenced by various factors, one of which is a lack of self-confidence ( self-efficacy ) regarding disease and health resulting in people not behaving in accordance with health values ​​​​and not having a good quality of life. The aim of writing this systematic review is to determine the relationship between self-management and efficacy on the quality of life in diabetes mellitus patients. The method used is a literature search with systematic review (PRISMA) as the standard for conducting a systematic review. Search articles using several journal databases, namely Google Scholar, Science Direct, and Clinicalkey, spanning a period of 5 years (2020-2024) with the keywords " Self Management " or " Self Efficacy " or "Quality of Life" or "Diabetes Mellitus ". Articles that were ready to be reviewed were 15 articles out of 3,704 articles obtained using PRISMA. The results of a systematic review study show that there is a relationship between self-management and self-efficacy and quality of life in diabetes mellitus patients. It is hoped that diabetes sufferers will regularly exercise confidence in implementing Self Management and Self Efficacy behavior with preventive efforts in the occurrence of diabetes mellitus complications. This must also be influenced by the good quality of life of diabetes mellitus sufferers.